Digital Competencies and Job Happiness: A Correlational Study in the Ecuadorian Digital Economy (Sociología y tecnociencia, 2026)
Given the advancement of digitalization and the importance of human talent retention, this study examines the relationship between digital competencies and job happiness in the Ecuadorian digital economy. Using a descriptive and correlational design, an online survey was conducted with 389 workers. The analysis revealed a moderate-to-high positive association (Rho = 0.624; p < 0.001) between both variables. Additionally, educational level and work experience influence these perceptions. The study concludes that digital competencies enhance workplace integration and job satisfaction, though experimental or longitudinal studies are needed to establish causal relationships